Determining the Ideal Election Model at the Provincial Level: Case Study of the Southeast Sulawesi Regional Head Election in 2018 - Teguh Setyabudi; Sampara Lukman; Aries Djaenuri; Khasan Effendy (GoAcademica Research & Publishing, 2020)
This research was conducted to find the right model in the provincial head elections. This is based on the many deficiencies that occur when direct regional head elections are held such as multiple voter lists, logistical problems, low capacity of organizers, the emergence of SARA issues, strong money politics, bureaucratic politicization, and low participation in voting for the community (Pilkada Case Study Southeast Sulawesi 2018). This research encourages the alternative model of the governor and deputy governor election. Furthermore, if you want to be applied in Indonesia in general, more research needs to be done. First, improvements in the overall stages of governors and deputy governors' elections and the use of information technology to increase transparency, accountability, and efficiency. Second, the governor and the deputy governor's election is still carried out directly by tightening the nomination requirements. Among other things, they must participate in the regeneration of political parties, have experience and knowledge of government and local characteristics of the region, and are indigenous people who have lived long in the area. Third, the governor is still directly elected by the community, while the deputy governor can be proposed by the governor to the DPRD/MOHA from the private sector/ASN who meet special requirements, namely experience in government and knowledge of the local characteristics of the region.